2014
DOI: 10.13075/mp.5893.2014.017
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Occupational Infections Caused by Borrelia Burgdorferi Among Forestry Workers and Farmers

Abstract: The risk of occupational exposure to the B. burgdorferi infection is high for foresters and farmers, and the infection with spirochetes is frequently confirmed on the basis of positive results of the Wb test. The presence of specific antibodies against protein antigens of B. spielmanii and B. bavariensis suggest that these bacteria can cause Lyme disease both independently and in participation with other Borrelia species, which influences the development of the clinical manifestations of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…They range from 19.2% to 61.5% in analyses performed with the ELISA test, depending on the region [16]. In examinations of foresters from the same area as in this study, the ELISA assay showed a positive or borderline result in at least one class of antibodies in 75% individuals, whereas verification with the Western blot test confirmed the results in 55% (IgM 15%, IgG 46%) [19].…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…They range from 19.2% to 61.5% in analyses performed with the ELISA test, depending on the region [16]. In examinations of foresters from the same area as in this study, the ELISA assay showed a positive or borderline result in at least one class of antibodies in 75% individuals, whereas verification with the Western blot test confirmed the results in 55% (IgM 15%, IgG 46%) [19].…”
Section: Discussionsupporting
confidence: 49%
“…In examinations of farmers from the Lublin region (ELISA test), the presence of antibodies from at least one class (IgM or IgG) was detected among 27.3% of the individuals [6]. Further reports from the same region demonstrated the presence of specific antibodies detected using the Western blot method in 33.0% of farmers [7]. Examinations of farmers from the same area as in this study revealed a positive or borderline result in at least one of the antibody classes in 42% of individuals examined using the ELISA test and in 28% of farmers after verification with the Western blot test (IgM 14%, IgG 18%) [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data concerning the frequency of occurrence of specific anti-B. burgdorferi antibodies in the groups I and II was published earlier [7,8].…”
Section: Resultsmentioning
confidence: 99%